Optimization of state regulation in the field of safety and security of business: a local approach - Kryshtanovych, Myroslav; Panfilova, Tetiana; Khomenko, Andrii; Dziubenko, Oleg; Lukashuk, Liubov (Business: Theory and Practice, 2023)
The main purpose of the study is to optimize local aspects of state regulation of ensuring the safety and security of enterprises in the context of sustainable development in a particular region. For this purpose, a new methodical approach was presented using simulation optimization of the processes of ensuring safety and security of security of enterprises in the context of sustainable development. The study focuses on enterprises and their safety and security systems security in the context of sustainable development. The relevance of the study is given by the fact that most enterprises in many regions suffer from ineffective regulation at the local level. At the same time, in most cases, state regulation does not take into account all aspects of safety and security in the context of sustainable development. The research methodology involves the use of a modern method of process optimization modeling. As a result, a model for optimizing local aspects of state regulation of business safety and security for a specific, selected region in the context of sustainable development was presented. The research has limitations and they consist of the selection of only one region and the consideration of local aspects of enterprises of certain socio-economic systems. Prospects for further research will be devoted to expanding modeling and taking into account a larger number of enterprises in the context of sustainable development.